Gregory Crewdson brief encounters - Kaproff, Dana 1954- (Zeitgeist Films Ltd., 2013)
Documentary about photographer, Gregory Crewdson. Crewdson's work is inspired by film, individuals such as, Alfred Hitchcock, David Lynch, Edward Hopper, and Diane Arbus, plus small-town America. His creations incorporate large film-production type crews that stage the scene down to the minute detail. This film was shot with "over a decade of unprecedented access."
Original: USA 2012
Bildformat 1.78:1
Special features: HD transfer, enhanced for widescreen viewing ; deleted scenes of Gregory Crewdson photo shoots ; additional interviews with Crewdson, Russell Banks, Rick Moody, and more ; Film Independent at LACMA Q&A with director Ben Shapiro, Crewdson and writer Jonathan Lethem in conversation with Elvis Mitchell ; original theatrical trailer ; optional subtitles for the deaf and hearing impaired (SDH)
Keywords: Crewdson, Gregory -- 1962-; Fotografie; Kleinstadt -- Motiv; USA; Film; DVD-Video